Question
upstudy study bank question image url

The function \( f(x)=\frac{5 x+7}{x-9} \) is one-to-one. a. Find an equation for \( f^{-1}(x) \), the inverse function. b. Verify that your equation is correct by showing that \( f\left(f^{-1}(x)\right)=x \) and \( f^{-1}(f(x))=x \). a. Select the correct choice below and fill in the answer box(es) to complete your choice. (Simplify your answers. Use integers or fractions for any numbers in the expression.) B. \( f^{-1}(x)=\square \), for all \( x \) C. \( f^{-1}(x)=\square \), for \( x \neq \square \) Dor \( x \geq \square \)

Ask by Horton Stewart. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The inverse function is \( f^{-1}(x) = \frac{9x + 7}{x - 5} \).

Solution

To find the inverse function \( f^{-1}(x) \) for the function \( f(x) = \frac{5x + 7}{x - 9} \), we will follow these steps: ### Step 1: Find the Inverse Function 1. **Replace \( f(x) \) with \( y \)**: \[ y = \frac{5x + 7}{x - 9} \] 2. **Swap \( x \) and \( y \)**: \[ x = \frac{5y + 7}{y - 9} \] 3. **Solve for \( y \)**: - Multiply both sides by \( y - 9 \): \[ x(y - 9) = 5y + 7 \] - Distribute \( x \): \[ xy - 9x = 5y + 7 \] - Rearrange to isolate terms involving \( y \): \[ xy - 5y = 9x + 7 \] - Factor out \( y \): \[ y(x - 5) = 9x + 7 \] - Solve for \( y \): \[ y = \frac{9x + 7}{x - 5} \] Thus, the inverse function is: \[ f^{-1}(x) = \frac{9x + 7}{x - 5} \] ### Step 2: Verify the Inverse Function Now we will verify that \( f(f^{-1}(x)) = x \) and \( f^{-1}(f(x)) = x \). #### Verification 1: \( f(f^{-1}(x)) \) 1. Substitute \( f^{-1}(x) \) into \( f(x) \): \[ f\left(f^{-1}(x)\right) = f\left(\frac{9x + 7}{x - 5}\right) \] - Substitute into the original function: \[ f\left(\frac{9x + 7}{x - 5}\right) = \frac{5\left(\frac{9x + 7}{x - 5}\right) + 7}{\left(\frac{9x + 7}{x - 5}\right) - 9} \] - Simplify the numerator: \[ = \frac{\frac{45x + 35}{x - 5} + 7}{\frac{9x + 7}{x - 5} - 9} \] - Convert 7 to a fraction: \[ = \frac{\frac{45x + 35 + 7(x - 5)}{x - 5}}{\frac{9x + 7 - 9(x - 5)}{x - 5}} \] - Simplify: \[ = \frac{\frac{45x + 35 + 7x - 35}{x - 5}}{\frac{9x + 7 - 9x + 45}{x - 5}} = \frac{\frac{52x}{x - 5}}{\frac{52}{x - 5}} = x \] #### Verification 2: \( f^{-1}(f(x)) \) 1. Substitute \( f(x) \) into \( f^{-1}(x) \): \[ f^{-1}(f(x)) = f^{-1}\left(\frac{5x + 7}{x - 9}\right) \] - Substitute into the inverse function: \[ = \frac{9\left(\frac{5x + 7}{x - 9}\right) + 7}{\left(\frac{5x + 7}{x - 9}\right) - 5} \] - Simplify the numerator: \[ = \frac{\frac{45x + 63}{x - 9} + 7}{\frac{5x + 7}{x - 9} - 5} \] - Convert 7 to a fraction: \[ = \frac{\frac{45x + 63 + 7(x - 9)}{x - 9}}{\frac{5x + 7 - 5(x - 9)}{x - 9}} \] - Simplify: \[ = \frac{\frac{45x + 63 + 7x - 63}{x - 9}}{\frac{5x + 7 - 5x + 45}{x - 9}} = \frac{\frac{52x}{x - 9}}{\frac{52}{x - 9}} = x \] ### Final Answer Thus, the inverse function is: \[ f^{-1}(x) = \frac{9x + 7}{x - 5} \] The correct choice is: **B.** \( f^{-1}(x) = \frac{9x + 7}{x - 5} \), for \( x \neq 5 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the inverse function \( f^{-1}(x) \) for \( f(x) = \frac{5x + 7}{x - 9} \), we will follow some steps. First, let’s set \( y = f(x) \): \[ y = \frac{5x + 7}{x - 9} \] Now we’ll swap \( x \) and \( y \) to find the inverse: \[ x = \frac{5y + 7}{y - 9} \] Next, we need to solve for \( y \) in terms of \( x \). Multiply both sides by \( y - 9 \): \[ x(y - 9) = 5y + 7 \] \[ xy - 9x = 5y + 7 \] Rearranging gives us: \[ xy - 5y = 9x + 7 \] \[ y(x - 5) = 9x + 7 \] \[ y = \frac{9x + 7}{x - 5} \] Thus, \[ f^{-1}(x) = \frac{9x + 7}{x - 5} \] So the answer for part (a) is: B. \( f^{-1}(x)=\frac{9x+7}{x-5} \), for \( x \neq 5 \). Now let's verify that this is indeed the correct inverse. To verify \( f(f^{-1}(x)) = x \): Substituting \( f^{-1}(x) \) into \( f \): \[ f\left(\frac{9x + 7}{x - 5}\right) = \frac{5\left(\frac{9x + 7}{x - 5}\right) + 7}{\left(\frac{9x + 7}{x - 5}\right) - 9} \] Calculating this, we simplify to get back to \( x \). For \( f^{-1}(f(x)) = x \): Substituting \( f(x) \) into \( f^{-1} \): \[ f^{-1}(f(x)) = f^{-1}\left(\frac{5x + 7}{x - 9}\right) = \ldots = x \] After simplification, this also yields \( x \). Both equations confirm that the found inverse is correct!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy